Human-Animal Interaction in Post-Tsunami Japan - Kajiwara, Hazuki (Humanimalia, 2016)
This paper explores the interaction between humans and their companion animals after the large tsunami which hit the northeast coast of Japan on 11 March 2011. Interviews, observation and fieldwork were used to assemble ethnographic accounts for 35 owners of companion animals who were assigned to temporary housing complexes where they are still living. A notion of “companion animal first” could be detected in the data.  This way of thinking might be defined as an ethical stance whereby the companion animal is given a very high value or net worth. Since there are few studies on companion animal in Japan at times when large-scale natural disasters occur, this research may contribute to the small but growing amount of qualitative research on human-animal relationships and interaction during and after disasters in an Asian country, thereby adding a sense of urgency to the need for comparative research in this important sphere of social life in most societies.